Família, dignidade e afeto: possibilidades e limites jurídicos para estabelecimento de múltiplos laços parentais - Cavalcanti, André Cleófas Uchôa (2007)
This work intends to investigate the mutations faced inside the families in history s, and how this changing may open the idea of multi kinship; on other words, the existence of a plurality of fathers and mothers on its relationship with a child. The investigation here is delimited by a western contemporary tradition, and, despite its transdisciplinary pretension, the work will be related mostly to Philosophy, Sociology, Politics and Law (and in the Law discipline, Constitutional Law, Civil Law, and specialy Families Law). Technically, the work will have as a basis the contemporary juridical legal order in Brazil. The hypothesis goes on the sense that is completely possible, using the principles adequately mainly the dignity and child s best interest principles - the uprising of new criterion about the link between children and parenthood, including in a multiple way. In this line, the Law may recognize and ordinate the new situations generated in society s core in XX century softening the cognitive closing specific of certain Law domains, like de Family Law